Advances in CMP/polishing technologies for the manufacture of electronic devices - Doi, Toshiro K., 1947-; Marinescu, Ioan D.; Kurokawa, Syuhei (Oxford : Elsevier, 2012)
CMP and polishing are the most precise processes used to finish the surfaces of mechanical and electronic or semiconductor components. --P. 4 of cover.
Includes bibliographical references and index.
Keywords: Grinding and polishing; Chemical mechanical planarization; Electrolytic polishing